Answers

The Brainliest Answer!
2014-04-30T14:39:13+05:30
If alpha,beta are roots of a quadratic equation ax^2+bx+c=0,then
alpha+beta=-b/a
alpha*beta=c/a
Therefore,alpha sq.+beta sq. =(alpha+beta)^2-2.alpha.beta
                                       =(-b/a)^2-2*c/a
                                       =b^2/a^2-2c/a
                                       =(b^2-2ac)/a^2
2 5 2
2014-05-01T11:39:53+05:30
As α and β are the roots
and u know
α+β=-b/a
αβ=c/a
α²+β²=(α+β)²-2αβ=
= \frac{b^2}{a^2}- \frac{2c}{a} = \frac{b^2-2ac}{a^2}
1 5 1